Eye Donation: Knowledge, Beliefs, Awareness, and Willingness Among Ambulance Drivers in Central India - Joshi RS; Goel P; Adatiya VH; Seth AS; Rasal AV (Clinical Ophthalmology, 2023)
Rajesh Subhash Joshi, Pranshu Goel, Vaishnavi Hitesh Adatiya, Ayushi Sanjay Seth, Ashwini Vitthalrao Rasal Department of Ophthalmology, Government Medical College, Nagpur, Maharashtra, 440003, IndiaCorrespondence: Rajesh Subhash Joshi, Department of Ophthalmology, Government Medical College, Nagpur, Maharashtra, 440003, India, Email jrajesh5@rediffmail.comAim: To determine the awareness about and willingness to donate eyes among ambulance drivers in Central India.Design: Prospective, observational, noncomparative, and cross-sectional survey study.Setting: Tertiary eye care center in Central India.Methods: The present study used a structured questionnaire distributed to ambulance drivers during the eye donation fortnight (August 25–September 8, 2022). The questionnaire comprised four domains: awareness, knowledge beliefs, and willingness to donate eyes. The collected data were entered into an Excel sheet and analyzed using SPSS software.Results: Forty-seven ambulance drivers participated in the study. All participants were men. The results showed that 48.9% (n = 23) of the ambulance drivers had completed elementary or middle school education. Furthermore, 27 (57%) participants were aware of eye donation; however, only 14 (29.7%) realized its importance. The source of information was mobile phones (n = 20, 42.6%). The common reason for the nondonation of eyes was lack of awareness (n = 14 29.7%). Thirty-five (74.5%) ambulance drivers were willing to donate their eyes, and the most common reason was the gratification derived from helping blind people.Conclusion: The study revealed the need to improve awareness and knowledge about eye donation among the participants. Arranging short sessions round the year, addressing the myths associated with eye donation, and sharing motivational stories may help create awareness. Display of information and booklets on eye donation in the ambulance is likely to help in obtaining more corneas for transplantation.Keywords: corneal transplantation, eye donation, eye donation fortnight, awareness of eye donation